Risk factors for development of lower limb osteoarthritis in physically demanding occupations: A systematic review and meta-analysis. (July 2020) - Canetti, Elisa F.D.; Schram, Ben; Orr, Robin M.; Knapik, Joseph; Pope, Rodney
Abstract: This systematic review and meta-analysis identified and critically reviewed the findings of recent studies (last 15 years) examining relationships between specific physically demanding occupations or occupational tasks and development of lower limb osteoarthritis (OA). Twenty-eight studies with 266, 227 cases of lower limb OA were included. Occupational tasks contributing to OA included farming, floor laying, and brick laying. Activities significantly contributing to the risk of knee OA were lifting heavy loads (>10 kg/week) (odds ratio [OR] = 1.52, 95% confidence interval [95%CI] 1.29–1.79), squatting/kneeling (OR = 1.69, 95%CI 1.15–2.49), standing (>2 h/daily) (OR = 1.22 95%CI 1.02–1.46) and walking (OR = 1.40 95%CI 1.14–1.73). Lifting contributed significantly to the risk of hip OA (OR = 1.35, 95%CI 1.16–1.57). The effects of occupational exposures appear to be magnified by previous injury and BMI >25 kg/m 2 . Since specific occupational activities increase OA risk, ergonomist should encourage the use of existing tools, or oversee the design of new tools that may decrease exposure to such activities. Highlights: Physically demanding occupations increased the risk of lower limb OA development. Occupational tasks were associated with lower limb OA. Squatting/kneeling, lifting/carrying and walking tasks increased risk of knee OA. Hip OA was associated with lifting tasks.